Obtaining an animal welfare status in Norwegian dairy herds—A mountain to climb - Barry, Conor; Ellingsen-Dalskau, Kristian; Garmo, Randi Therese; Grønmo Kischel, Stine; Winckler, Christoph; Kielland, Camilla (Frontiers in Veterinary Science, 2023)
Knowing the national status of animal welfare, one can identify welfare problems and set a benchmark against which improvements can be compared. Such a status is potentially invaluable for tangible, sustained animal welfare improvement. The objective of this cross-sectional study was to report the status of animal welfare in Norwegian loose-housed dairy herds as assessed using the Welfare Quality® Assessment Protocol. Additionally, we investigated if the welfare status varied on a regional basis. In total, 155 herds in eight of Norway’s eleven counties were assessed by six trained Welfare Quality® assessors. This article presents the herd prevalences of common welfare issues in dairy production in Norway, as well as integrated welfare scores. To determine whether welfare status varied regionally in Norway, generalized linear modelling was used to estimate the mean welfare score for five regions in the four Welfare Quality® principles: A. Good feeding, B. Good housing, C. Good health, and D. Appropriate behaviour. These estimated mean welfare scores and their 95% confidence intervals were subsequently assessed for significant variation. Encouraging findings included the low mean herd prevalence of ‘very lean’ cows (3.0%) and the high proportion of cows (59.8%) which could be touched during avoidance distance testing, indicating a positive relationship between stockpeople and their cattle. Challenges affecting the welfare of Norwegian dairy cows were also identified. Of particular concern were issues related to the cows’ environment such as prolonged times needed to complete lying down movements and integument alterations. No herd was completely free of changes to the integument and, on average, 77.9% of each herd were affected either mildly or severely. Animal welfare did not appear to vary much between the five regions assessed. Our investigation revealed significant regional variation between two regions (Trøndelag and Vestlandet North) in only the Welfare Quality® principle Good housing (p < 0.01). The almost complete absence of regional variation demonstrates that animal welfare status generally varies most at herd level. In conclusion, both welfare challenges and encouraging findings were identified in loose-housed Norwegian dairy herds. To improve animal welfare, herd-specific interventions are most likely to be effective in these herds.